Breakdown of proteoglycan and collagen induced in pig articular cartilage in organ culture. - Dingle, J T (1975)
Explants of articular cartilage from young pigs were maintained in organ culture for 10--16 days, and degradation of matrix was induced by retinol or complement-sufficient antiserum. The percentage breakdown of proteoglycan and collagen (as hydroxyproline release) was measured. The response of the cartilage depended on whether or not the explants were cut so as to include some of the invading marrow ('invasion zone'). In media containing retinol, cartilage lost up to three-quarters of its proteoglycan whether the invasion zone was present or not, but very little of its collagen unless this region was included. In the presence of complement-sufficient anti-serum, however, cartilage without the invasion zone was virtually unaffected, but both proteoglycan and hydroxyproline were released when invasion zone was included; here proteoglycan release began almost immediately, but there was a time-lag of 6--8 days before a substantial amount of hydroxyproline appeared in the medium. Histological examination of sample explants from the experiments supported the biochemical findings. The possible significance of the results in relation to rheumatoid arthritis is discussed.